The Hidden Correlation between Intelligence and Autism - Yahya, Reema (2020)
In 2018, Centers for Disease Control and prevention (CDC) [26] determined that approximately 1 in 54 children in US is diagnosed with an autism spectrum disorder (ASD). Within this group of autistic children, 44% had IQ scores in the average to above average range (IQ >85). Moreover, various studies [4,5,6] show that many cases of prodigies or super talented children show some autistic traits, most notably in attention to details and problems in communication or social skills. The Objective of this study is to discover the connection between autism and extreme talent (i.e. intelligence). In this research, cytoscape was used for visualizing and analyzing autism/intelligence genes’ interaction network. It has been found that there are some shared genes as well as a list of pathways demonstrating the strong correlation between Autism and Intelligence. Furthermore, strong contribution of some genes was observed in different pathways. For instance, EP300 was seen in motor delay and autistic behavior pathway. The same gene has a strong relation with Rubinstein Taybi syndrome. Glutamate-dependent receptors group were also seen in different pathways. This research has identified the shared genes and hubs (genes with high degree of connectivity) from statistical point of view. This document is divided into five chapters. Th first chapter of this thesis introduces Autism or Autism spectrum disorder (ASD). The second chapter covers a literature review on the available studies. The third chapter discusses the methodology used to explore the assumed genetic correlation between autism and intelligence. It also introduces and discusses the main tools, applications and databases used in this research. The fourth chapter focuses on analyzing the genetic pathways that are represented in genetic interaction networks. The last chapter (chapter 5), provides the conclusion for the conducted research.